Climate Change : Global Risks, Challenges and Decisions - Richardson, Katherine (Cambridge University Press, 2011)
"Providing an up-to-date synthesis of all knowledge relevant to the climate change issue, this book ranges from the basic science documenting the need for policy action to the technologies, economic instruments and political strategies that can be employed in response to climate change. Ethical and cultural issues constraining the societal response to climate change are also discussed. This book provides a handbook for those who want to understand and contribute to meeting this challenge. It covers a very wide range of disciplines - core biophysical sciences involved with climate change (geosciences, atmospheric sciences, ocean sciences, ecology/biology) as well as economics, political science, health sciences, institutions and governance, sociology, ethics and philosophy, and engineering. As such it will be invaluable for a wide range of researchers and professionals wanting a cutting-edge synthesis of climate change issues, and for advanced student courses on climate change"--